2019
DOI: 10.1021/acs.jpclett.9b03217
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Liquid Phase Transformation of an Ionic Liquid N,N,N-Trimethyl-N-propylammonium Bis(trifluoromethanesulfonyl)imide

Abstract: An ionic liquid, N,N,N-trimethyl-N-propylammonium bis­(trifluoromethanesulfonyl)­imide (TMPA TFSI), was transformed from a liquid phase to another fluidic phase by application of the threshold magnetic field at constant temperature (T). The magnetic-field-induced (MFI) phase transformation was detected by the electric potential generated between two Pt electrodes set to the bottom and upper parts in a TMPA TFSI liquid during sweep of the magnetic field (B). The magnetic susceptibility and Verdet constant of TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We measured the Hall voltage across the channel under a constant current while sweeping the magnetic field. To avoid temporal changes in the carrier density during the measurements, all measurements were performed at temperatures below the freezing point of the ionic liquid (~ 256 K) 23 .
Figure 2 FET and Hall measurements of the SWCNT thin film devices.
…”
Section: Resultsmentioning
confidence: 99%
“…We measured the Hall voltage across the channel under a constant current while sweeping the magnetic field. To avoid temporal changes in the carrier density during the measurements, all measurements were performed at temperatures below the freezing point of the ionic liquid (~ 256 K) 23 .
Figure 2 FET and Hall measurements of the SWCNT thin film devices.
…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical and experimental observations show that a first-order LLT can occur without a noticeable density change, making this phenomenon even more puzzling 19 . Furthermore, magnetic field can affect the local structure and lead to another liquid phase 20 . It was reported that an aligned liquid state of Co alloys can be transformed into another liquid phase under magnetic fields 21,22 .…”
mentioning
confidence: 99%